2021
DOI: 10.3390/app11219862
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Concrete Made with the Addition of Recycled Macro Plastic Fibres

Abstract: For many decades, researchers have been working on finding innovative and sustainable solutions to address the enormous quantities of plastic waste that are produced every year which, after being collected, are transformed into energy, recycled, or sent to landfills. Giving a second life to plastic waste as a material to be incorporated, in the form of macro-fibres, into concrete, could be one such solution. The purpose of this study was to analyse the mechanical and physical behaviour of the hardened concrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Therefore, replacing more aggregates with plastic waste resulted in weak adhesion between the plastic and cement paste [ 17 , 43 ]. Other researchers suggested a zone formation and void (or air) content, where stress is concentrated, leading to failure [ 16 , 29 , 44 ]. Merlo et al [ 16 ] suggested that plastic fillers, due to their relatively low mechanical properties and poor adhesion, behave as porosities in the aggregate, which weakens the mortar matrix.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, replacing more aggregates with plastic waste resulted in weak adhesion between the plastic and cement paste [ 17 , 43 ]. Other researchers suggested a zone formation and void (or air) content, where stress is concentrated, leading to failure [ 16 , 29 , 44 ]. Merlo et al [ 16 ] suggested that plastic fillers, due to their relatively low mechanical properties and poor adhesion, behave as porosities in the aggregate, which weakens the mortar matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The re-use of plastics, particularly in construction, is gaining momentum, because it can potentially provide a solution to minimize environmental pollution by preventing plastic waste being dumped in landfills and incinerated. Studies suggest that plastic waste can be used in concrete as a partial substitute for sand and coarse aggregates, such as polyethylene terephthalate (PET) [ 7 , 8 , 9 , 10 , 11 , 12 ], polystyrene (PS) [ 13 , 14 ], polyvinyl chloride (PVC) [ 15 , 16 , 17 , 18 , 19 ], high-density polyethylene (HDPE) [ 20 , 21 , 22 , 23 ], low-density polyethylene (LDPE) [ 24 , 25 , 26 , 27 ], and blends of different polymers [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, recycling shredded composites can produce new polymer composites, utilising high-quality glass fibres and reducing reliance on virgin materials [13,18,35,36]. Moreover, the shredded composites can replace synthetic macro fibres in concrete, improving its tensile strength and crack resistance [37][38][39]. Additionally, the composites can produce fused filaments for 3D-printed parts, resulting in increased structural performance [40,41].…”
Section: Cutting Shredding and Grindingmentioning
confidence: 99%
“…Not much research has been done on the use of waste PET extruded fibres in process flow followed in the production of textile grade fibres and use of fly ash on concrete. Much research has been done on filaments and fibres produced by either simple shredding or cutting up PET bottles to use as reinforcement of concrete [21][22][23]. The present study evaluates the effect of hybridization of both fly ash and PET fibres in a fibre reinforced concrete composite (FRCC) and ascertains the mechanical strength effects of varying the mass fractions of these.…”
Section: Introductionmentioning
confidence: 99%